„Ich habe […] keine Sonate schreiben wollen, sondern einen Roman“ – zu autoreferenziellen Aspekten von Thomas Manns Doktor Faustus - Kotin, Andrey (Studia Germanica Posnaniensia, 2013)
In the centre of the analysis stands the autoreferential dimension of Thomas Mann’s Doktor Faustus and its relation to the novel’s socio-philosophical message, which, although not free from ironical overtones, tends to be a didactic plea for humanism. However, the main emphasis of the investigation is not the humanist idea itself but, above all, the narrative methods used to infuse this idea with new means of expression. Therefore, the music-motif in the novel is interpreted as a metaphor of an intertextual literary motif. From a metaliterary perspective, the main question in Mann’s partly consistent, yet partly paradoxical art- and soul-study is the following: how can (and should) the Faust-legend be reshaped and interpreted to match the demands of the modern age? The attempt to discuss the ‚national myth‘ in such a new way is made by three authorities: two fictional and one real. The protagonist, Adrian Leverkühn, the first-person narrator, Serenus Zeitblom, and, finally, the author himself, Thomas Mann, each in turn, whether wilfully or unconsciously, offers their own art-concept. To a great extent, the general semantic picture of the story told in Faustus is determined by various distinctions between the intratextual ideological confrontation ‚Leverkühn vs. Zeitblom‘ and the extratextual outside-perspective of the author, who stays paramount to the novel-figures. My article attends to the narratological as well as the philosophical decoding of this overall-picture.